Voyages and beaches : Pacific encounters, 1769-1840 - Calder, Alex; Lamb, Jonathan, 1945-; Orr, Bridget; David Nichol Smith Memorial Seminar 1993 : University of Auckland) (Honolulu : University of Hawai'i Press, 1999)
What actually happened as Europeans and peoples of the Pacific discovered each other? How have their respective senses of the past influenced their understanding of the present? And what are the consequences of their meeting? In this collection of essays, scholars from European, Polynesian, and Settler backgrounds provide answers to these questions. Writing from, and between, a variety of disciplines (history, anthropology, Maori Studies, literary criticism, law, cultural studies, art history, Pacific Studies), they show how the Pacific reveals a more various and contradictory history than that supposed by such homogenizing metropolitan myths as the introduction of civilization to savage peoples, the general ruin of indigenous cultures by an imperial juggernaut, or the mimicry of European models by an abject population. They examine contact from both sides of beaches throughout Polynesia, exposing the many inconsistencies from which Pacific history is made. Some of the essays consider the extent to which traditional European ideas about organizing and legitimizing claims to territory and power were invoked and problematized in the South Pacific; some consider the violence endemic in such scenes; others examine the aesthetic discourses with which early travelers and settlers attempted to make sense of the Pacific in the aftermath of "discovery." But rather than reiterate the myths and anti-myths of conquest, these essays show how local differences have made and do make a difference. They emphasize the Pacific's capacity to absorb and transform the impact of Europe, an impact that has been as notable for its ambivalence and confusion as for its single-minded pursuit of hegemony. The editors develop these themes in a wide-ranging introduction that relates Pacific concerns to a more global set of theoretical and methodological problems, including current work in post-colonial and subaltern studies
Introduction : postcoloniality and the Pacific / Alex Calder, Jonathan Lamb and Bridget Orr -- Nature and history, self and other : European perceptions of world history in the age of encounter / J.G.A. Pocock -- South Pacific mythology / 'I.F. Helu -- The postmodern legacy of a premodern warrior goddess in modern Samoa / Malama Meleisea -- Myth and history / 'Okusitino Māhina -- A history lesson : Captain Cook finds himself in the state of nature / Stephen Turner -- Myth, science and experience in the British construction of the Pacific / David Mackay -- A tribal encounter : the presence and properties of common-law language in the discourse of colonization in the early modern period / P.G. McHugh -- Liberty and license : the Forsters' accounts of New Zealand sociality / Nicholas Thomas -- Early contact ethnography and understanding : an evaluation of the Cook expeditionary accounts of the Grass Cove conflict / Ian G. Barber -- My musket, my missionary and my Mana / Pat Hohepa -- Enlightenment anthropology and the ancestral remains of Australian aboriginal people / Paul Turnbull -- Missionaries on Tahiti, 1797-1840 / Rod Edmond -- Augustus Earle's The meeting of the artiest and the wounded Chief Hongi, Bay of Islands, New Zealand, 1827 and his depictions of other New Zealand encounters : contexts and connections / Leonard Bell -- Categorical weavings : European representations of the architecture of Hakari / Sarah Treadwell -- Pacific colonialism and the formation of literary culture / Simon During -- The canon on the beach : H.T. Kemp translating Robinson Crusoe and The pilgrim's progress / Mark Houlahan -- Tuku Whenua and land sale in New Zealand in the nineteenth century / Margaret Mutu.
Papers presented at the 9th David Nichol Smith Memorial Seminar, University of Auckland, 1993.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Oceania -- Discovery and exploration -- Congresses; Océanie -- Découverte et exploration -- Congrès.; HISTORY; HISTORY -- Australia & New Zealand; Discoveries in geography; Oceania; Entdeckung; Kultur; Sozialgeschichte; Kongress; Ozeanien; Cultuurcontact; Europeanen; Kolonisatie; Congress; proceedings (reports); Conference papers and proceedings; Congressen (vorm); Conference papers and proceedings; Actes de congrès.